More tales for trainers : using stories and metaphors to influence and encourage learning - Parkin, Margaret (Kogan Page, 2010)
More Tales for Trainers is an introduction to using stories, anecdotes, metaphors and poetry to give training programmes more impact. It includes 50 tales that trainers can use in a variety of training such as communication, leadership, and problem-solving.